Intramedullary Fixation With a Short Nail in a Young Patient Presenting With a Pathological Proximal Femur Fracture. (June 2021) - Roberto González, Marcos; Bryce-Alberti, Mayte; Subhawong, Ty; Hakim, Muhammad; Rosenberg, Andrew; Pretell-Mazzini, Juan
Abstract : An 18-year-old man presented with a pathological fracture of the right proximal femur. Desmoplastic fibroma was diagnosed through histological studies. Surgical management involved extended intralesional curettage and fracture stabilization by open reduction with intramedullary nailing, using a short Gamma nail. At 42-month follow-up, the patient presented no limitations or recurrence. Internal fixation after prior intralesional curettage is a valid treatment strategy for pathological fractures in young patients. A short nail was chosen to prevent direct tumor cell seeding throughout the femur and future recurrence. Fracture consolidation was achieved because of the healing potential of a young patient.